2021
DOI: 10.1002/ecy.3600
|View full text |Cite
|
Sign up to set email alerts
|

Broad aggressive interactions among African carnivores suggest intraguild killing is driven by more than competition

Abstract: Theory on intraguild killing (IGK) is central to mammalian carnivore community ecology and top‐down ecosystem regulation. Yet, the cryptic nature of IGK hinders empirical evaluations. Using a novel data source – online photographs of interspecific aggression between African carnivores – we revisited existing predictions about the extent and drivers of IGK. Compared with seminal reviews, our constructed IGK network yielded 10 more species and nearly twice as many interactions. The extent of interactions increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…However, particularly in the protected area, small carnivore species tended to spatially avoid lions. This is in line the with recently uncovered susceptibility of small African carnivores to lion suppression (Curveira‐Santos et al, 2022 ; Curveira‐Santos, Sutherland, Tenan, et al, 2021b ). Unlike larger subordinate species, better equipped to escape and mitigate dangerous encounters while co‐occurring with the apex predator, for small carnivores spatial avoidance of lions may be a better strategy (Wirsing et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, particularly in the protected area, small carnivore species tended to spatially avoid lions. This is in line the with recently uncovered susceptibility of small African carnivores to lion suppression (Curveira‐Santos et al, 2022 ; Curveira‐Santos, Sutherland, Tenan, et al, 2021b ). Unlike larger subordinate species, better equipped to escape and mitigate dangerous encounters while co‐occurring with the apex predator, for small carnivores spatial avoidance of lions may be a better strategy (Wirsing et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…As such, it would be expected that the presence of leopard has a greater effect on caracal site use, as the two species are closer in body size and share a higher degree of dietary overlap (Müller et al 2022). However, recent studies have indicated that the network of intraguild competition and top-down mediated effects are more extensive than previously thought (Prugh and Sivy 2020;Curveira-Santos et al 2022). Intraguild competition increases under resource limitation (Palomares and Caro 1999), and with the depletion of natural prey (Munthali and Mkanda 2002) and the absence of a resident lion population in KNP (Davis et al 2021a), spotted hyaena may exert greater top-down influences on sympatric carnivores.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of caracal spatiotemporal responses to leopard presence is surprising, as the two species can display high dietary overlap (Müller et al 2022) and leopard are known to kill caracal when encountered (Curveira-Santos et al 2022). Given the potential for dietary overlap (Caro and Stoner 2003;Müller et al 2022), caracal and leopard may be selecting similar habitat characteristics for preferred prey, and this could explain the positive relationship between caracal site use and leopard abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we used criteria developed by Ratnayeke et al [20], to determine the severity of injuries sustained during sloth bear attacks. These were grouped into four categories: (1) minor injuries (injuries that did not result in deep punctures and only had minor scratches or superficial lacerations); (2) moderate injuries (injuries that resulted in deep punctures that took longer to heal and left few permanent scars); (3) moderately serious injuries (fractures of the hands or feet, punctures to the head, several lacerations or punctures that resulted in significant bleeding); and (4) serious injuries (injuries that resulted in fractured bones in the head or neck, loss of scalp, the removal of facial components (such as the eyes, nose, and ears), or the permanent impairment of one's vision, hearing, or speech.…”
Section: Data Preparation and Analysismentioning
confidence: 99%
“…Large carnivores' predatory, competitive, and aggressive nature in general plays an important role in shaping the structure and function of ecosystems that they inhabit [1][2][3]. As a result, large carnivores' population management is a major priority in today's conservation scenario, particularly in human-dominated settings where carnivore populations are diminishing [4].…”
Section: Introductionmentioning
confidence: 99%